2016
DOI: 10.3389/fonc.2015.00306
|View full text |Cite
|
Sign up to set email alerts
|

The rs11515 Polymorphism Is More Frequent and Associated With Aggressive Breast Tumors with Increased ANRIL and Decreased p16INK4a Expression

Abstract: Chromosome position 9p21 encodes three-tumor suppressors p16INK4a, p14ARF, and p15INK4b and the long non-coding RNA ANRIL (antisense non-coding RNA in the INK4 locus). The rs11515 single-nucleotide polymorphism in the p16INK4a/p14ARF 3′-untranslated region is associated with glioblastoma, melanoma, and other cancers. This study investigated the frequency and effect of rs11515 genotypes in breast cancer. Genomic DNA samples from 400 women (200 with and 200 without a diagnosis of breast cancer) were genotyped fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…9p21 deletions were associated with aggressive breast cancer including reduced survival and high grade of cancer progression (Jong et al, ; Seute et al, ; which may include genes such as CDKN2B ; 9p21; Erickson et al, ) and SH3GL2 (9p22; Sinha et al, ). Royds et al () conducted an investigation into the frequency and result of CDKN2A rs11515 genotypes in breast cancer. They showed an important connection between the genetic polymorphism with a very aggressive tumor that could be due to increase ANRIL and diminish p16INK4a expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9p21 deletions were associated with aggressive breast cancer including reduced survival and high grade of cancer progression (Jong et al, ; Seute et al, ; which may include genes such as CDKN2B ; 9p21; Erickson et al, ) and SH3GL2 (9p22; Sinha et al, ). Royds et al () conducted an investigation into the frequency and result of CDKN2A rs11515 genotypes in breast cancer. They showed an important connection between the genetic polymorphism with a very aggressive tumor that could be due to increase ANRIL and diminish p16INK4a expression.…”
Section: Discussionmentioning
confidence: 99%
“…Different polymorphisms have been reported in this locus (Zeggini et al, ). Different single nucleotide polymorphisms (SNPs) disturb the INK4b‐ARF‐INK4a locus and may alter the genes expression which may lead to silencing of the INK4b‐ARFINK4a locus through binding near their promoter (Royds et al, ). Previously, we showed the association of CDKN2A/B rs10811661 in 564 subjects suffering from breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of target genes in PBMCs were quantitatively assessed using Taqman® gene expression assays (Life Technologies) using the following inventoried primer/probes: for ANRIL , Hs01390879_m1; for p15 , Hs0079225_m1; for p14ARF , Hs99999189_m1; for p16 , Hs02902543_mH; for TP53 , Hs99999147_m1; for GAPDH (glyceraldehyde 3‐phosphate dehydrogenase) gene, 4333764‐0805024) . GAPDH was used as an endogenous reference for normalized gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…In combination with Polycomb Repressing Complexes 1 and 2 (PRC1 and 2), ANRIL negatively regulates the transcription of the entire INK4‐ARF locus (including p15 , p14ARF , and p16 genes), thus simultaneously modulating both the p53 and pRb pathways (Figure ) . Emerging evidence has shown that a number of single nucleotide polymorphisms (SNPs) in ANRIL are associated with susceptibility to different types of cancer and some degenerative diseases (such as type‐2 diabetes and atherosclerosis) …”
Section: Introductionmentioning
confidence: 99%
“…26 To confirm the presence and frequency of IDH1 mutations and to estimate the number of IDH2 mutations, exon 4 of IDH1 and IDH2 were amplified from tumor-extracted DNA and sequenced. 27 Tumor DNA was extracted from paraffin embedded tumor sections or frozen tumor.…”
Section: Mutant Idh1 and Idh2 Determinationmentioning
confidence: 99%